2014
DOI: 10.1016/j.joca.2013.11.002
|View full text |Cite
|
Sign up to set email alerts
|

Pro-inflammatory stimulation of meniscus cells increases production of matrix metalloproteinases and additional catabolic factors involved in osteoarthritis pathogenesis

Abstract: Objective Meniscus injury increases the risk of osteoarthritis; however, the biologic mechanism remains unknown. We hypothesized that pro-inflammatory stimulation of meniscus would increase production of matrix-degrading enzymes, cytokines and chemokines which cause joint tissue destruction and could contribute to osteoarthritis development. Design Meniscus and cartilage tissue from healthy tissue donors and total knee arthroplasties was cultured. Primary cell cultures were stimulated with pro-inflammatory f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

9
91
0
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 88 publications
(101 citation statements)
references
References 45 publications
9
91
0
1
Order By: Relevance
“…Using a gene microarray, we found that 30-kDa FN-f induces increased gene expression of several chemokines in meniscocytes and chondrocytes. In addition to confirming observations that FN-f increases expression of MMP1, MMP2, MMP3, MMP13, IL-6, and IL-8 in meniscocytes, 50 we have, for the first time, identified that FN-f also increases expression of MMP9 and CCL5, CCL20, and CXCL10 chemokines in human meniscocytes. Similar effects are evident in articular chondrocytes, although we found no change in MMP2 or MMP9 expression in these cells, consistent with findings by others.…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…Using a gene microarray, we found that 30-kDa FN-f induces increased gene expression of several chemokines in meniscocytes and chondrocytes. In addition to confirming observations that FN-f increases expression of MMP1, MMP2, MMP3, MMP13, IL-6, and IL-8 in meniscocytes, 50 we have, for the first time, identified that FN-f also increases expression of MMP9 and CCL5, CCL20, and CXCL10 chemokines in human meniscocytes. Similar effects are evident in articular chondrocytes, although we found no change in MMP2 or MMP9 expression in these cells, consistent with findings by others.…”
Section: Discussionsupporting
confidence: 87%
“…60 FN-f show potent catabolic activity in increasing expression of Toll-like receptors and inflammatory cytokines, including tumor necrosis factor (TNF)-a, interleukin (IL)-1b, and IL-1a; elevating production of matrix metalloproteinase (MMP) proteases; and suppressing proteoglycan synthesis. 13,19,20,49,51 FN-f are also released from articular cartilage after impact injury 7 and have been shown to increase production of MMPs by normal and OA meniscocytes in vitro, 50 indicating that a general increase in levels of these biologically active fragments in synovial fluid in OA or other joint disorders is also detrimental to meniscus structure and function.…”
mentioning
confidence: 99%
“…Over the course of OA development, catabolic factors, including proinflammatory cytokines, are activated, which induces the gradual self-destruction of cartilage coupled with the curb of chondrogenic differentiation (3)(4)(5). Accompanied with this process is the impact of non-cartilage-specific extracellular matrix (ECM) with inferior mechanical properties, which is produced by dedifferentiated chondrocytes and can prevent chondroprogenitors from remodeling cartilage defects through migration (6,7).…”
Section: Introductionmentioning
confidence: 99%
“…Interestingly, both FINC and CHI3L1 had been proposed as biomarkers of OA. FINC was first found to be increased in OA cartilage [38], and its proteolytic fragments have been extensively studied as catabolic players in OA pathogenesis, through the induction of cytokines and metalloproteinases (specifically MMP13) [39]. On the other hand, CHI3L1 (also known as cartilage glycoprotein YKL-40) is a major secretory protein from chondrocytes, whose levels in serum and synovial fluid are significantly increased in OA subjects [40], and also in OA cartilage [41].…”
Section: Two Cartilage Ecm-related Proteins Finc and Chi3l1 Are Incmentioning
confidence: 99%